গণমাধ্যমে বাংলাদেশের মুক্তিযুদ্ধ, ১ম খন্ড - আহমেদ, রিয়াজ. (ঢাকা : অনন্যা, 2008)
Articles, reports, and cartoons collected from various newspapers and news magazines on the 1971 liberation war of Bangladesh.
[v.] 1. K{macr}ar{dotb}tuna / sa{dotb}mkalana o samp{macr}adan{macr}a, Ri{dot}y{macr}aja {macr}Ahameda = Cartoons / compiled and edited by Reaz Ahmed -- v. 2. Selections from the Frontier / compiled and edited by Muntassir Mamoon -- 3. kha{dotb}n{dotb}da. Mujibanagara, mukt{macr}a{tilde}ncala o abaruddha B{macr}a{dotb}ml{macr}ade{acute}sa theke prak{macr}a{acute}sita patrapatrik{macr}a / sa{dotb}mkalana o samp{macr}adan{macr}a, H{macr}asi{macr}na {macr}Ahameda -- v. 4. Mujibanagara, mukt{macr}a{tilde}ncala, abaruddha B{macr}a{dotb}ml{macr}ade{acute}sa theke prak{macr}a{acute}sita patrapatrik{macr}a / sa{dotb}mkalana o samp{macr}adan{macr}a, H{macr}asi{macr}na {macr}Ahameda -- v. 5. Mujibanagara, mukt{macr}a{tilde}ncala o abaruddha B{macr}a{dotb}ml{macr}ade{acute}sa theke prak{macr}a{acute}sita patrapatrik{macr}a / sa{dotb}mkalana o samp{macr}adan{macr}a, H{macr}asin{macr}a {macr}Ahameda -- v. 6. Dainika {macr}Anandab{macr}aj{macr}ara patrik{macr}a theke sa{dotb}mkalana -- v. 7. Dainika {macr}Anandab{macr}aj{macr}ara patrik{macr}a theke sa{dotb}mkalana / sa{dotb}mkalana o samp{macr}adan{macr}a, Munat{macr}as{macr}ira M{macr}amuna -- v. 8. Dainika {macr}Anandab{macr}aj{macr}ara patrik{macr}a theke sa{dotb}mkalana -- v. 9. Mujibanagara, mukt{macr}a{tilde}ncala, o abaruddha B{macr}a{dotb}ml{macr}ade{acute}sa theke prak{macr}a{acute}sita patrapatrik{macr}a / sa{dotb}mkalana o sam{macr}padan{macr}a, H{macr}asin{macr}a {macr}Ahameda
Vol. 4-9 published by Anany{macr}a, Dhaka.
গ্রন্থপুঞ্জিগত নির্দেশিকা ও ইনডেক্স.
Bengali and English; v. 2 in English.
Keywords: India-Pakistan Conflict, 1971 -- Mass media and the conflict; Bangladesh -- History -- Revolution, 1971.; Bangladesh -- History -- Revolution, 1971 -- Mass media and the revolution